Experimental activity at test rig validating correlations to select pumps running as turbines in microhydro plants. (1st October 2017) - Barbarelli, S.; Amelio, M.; Florio, G.
Highlights: The authors present measurements at test rig of 12 pumps running as turbine. The pump operating mode of these machines has been correlated to that as turbine. A procedure selecting the best pump as turbine for a hydrological site is set up. The procedure is recursive giving the possibility to refine the preliminary choice. An exemplificative case study is illustrated with the aim to explain the procedure. Abstract: The use of hydraulic pumps running as turbines offers several advantages with respect to traditional turbines. The possibility of predicting the performances of a pump running as a turbine and of selecting the suitable machine for a given hydropower site, in an easy and reliable way, is a still open issue. The present work makes a contribution to the solution of this subject both through experimental and theoretical activities. The experimental activity is carried out by the characterisation of 12 pumps measured, at test rig both in their natural operation, as pumps and in reverse mode, as turbines. The numerical activity starts from the definition of correlations regarding the heads and capacities conversion factors, useful for the preliminary selection of a suitable pump to run as turbine in a microplant for a given hydropower site. Then, a statistical method involving polynomials was implemented, allowing the performance curves to be provided. The agreement between experimental data and numerical results is comparable to that obtained by others authors. Finally, a comprehensive procedure has been set up, refining the selection by evaluating likewise if the efficiency of the selected pump to use as a turbine, at operating point of the proposed plant, is acceptable. The results related to a study case are shown with the aim to highlight the easiness of the proposed method, having in mind that it does not represent the generality of the possible applications of pumps running as turbines.